Investigation on the Properties of Oil Palm Shell Concrete in Comparison to Normal Weight Concrete - Filipe, Waqabitu (2017)
This research involves the investigation of Oil Pal Shell (OPS) as an aggregate component in lightweight concrete. The aim of this research project is to utilise OPS in the production of light weight concrete and determine whether the properties of OPS concrete is suitable for it to be used in construction. There are various physical and mechanical test that were to be conducted on OPS Concrete along with a control samples of normal weight concrete (NCW). One of the most important factors that is being considered in this project, is the weight of the OPS concrete in comparison to that of the NWC. Therefore, the theoretical densities were determined from the mix design, and then it was determined experimentally by weighing of the concrete test cubes. Since this project is investigating a lightweight concrete, the Department of Environment (DOE) method for concrete mix design, can only be used for determining the mix design of the control samples of NWC. For OPS concrete, trial mixes need to be conducted to determine the concrete mix proportions. The OPS concrete and the NWC were all designed to 30MPa. Three trial batches of OPS concrete were conducted with varying amounts of OPS; namely 65%, 80.5%, 78.4% and these proportions were selected on trial and error basis. Superplasticiser was also used in two concrete batches (One OPS concrete batch and one NWC batch) to aid in workability at low water/cement ration. The mechanical testing involved compression test and slump test to determined workability. All specimens were cured in water and the samples were tested for compressive strength on the day 7, 14 and 28.